Study of Renal enzymuria and albuminuria activity in the Petals of Pink Nelumbo nucifera Gaertn. - R. V. Saraswathi, F. Gricilda Shoba (Journal of Applied Pharmaceutical Science, 2015)
Aim: The aim of the present study was to assess the activity of Nelumbo nucifera Gaertn. Petal extract (NNPE) in tubular enzymes and in urinary albumin of Gentamicin (GM) induced renotoxic rats. Material and methods: The study was conducted for fourteen days in twenty-four rats in four groups and the study was designed as ,Group I: Control group received 0.5% CMC; Group II: GM 100mg/kg/day i.p. Group III: NNPE extract (200mg/kg/day p.o.) + GM (100mg/kg/day i.p.); Group IV: NNPE extract (400mg/kg/day p. o) + GM (100mg/kg/day i.p.).After the last injection of GM, 24-hour urine samples were collected from all the groups to analyze the levels of tubular marker enzymes N-acetyl-β-D-glusosaminidase (NAG), Gama Glutamyl transpeptidase (GGT), Alkaline phosphatase (ALP) and Lactate dehydrogenase (LDH) and Albumin in urine to determine the extent of renal tubular damage by measuring renal enzymuria and albuminuria in toxic rats induced by Gentamicin.Results: Levels of tubular marker enzymes and albumin were increased in Group-II and in treatment with N. nucifera Gaertn. Petal extract with different doses brought back to normal levels in tubular marker enzymes as well as albumin in urine for Group- III and Group- IV.Conclusions: The present study revealed that N. nucifera Gaertn. Petal extract possess potent protective effect in both doses due to its high antioxidant property against renal enzymuria and albuminuria.
Keywords: Albuminuria, Gentamicins, Kidney Tubules, Nelumbo, Rats.